2016
DOI: 10.1371/journal.pmed.1002095
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk Factor Changes Observed in Diabetes Prevention Programs in US Settings: A Systematic Review and Meta-analysis

Abstract: BackgroundThe Diabetes Prevention Program (DPP) study showed that weight loss in high-risk adults lowered diabetes incidence and cardiovascular disease risk. No prior analyses have aggregated weight and cardiometabolic risk factor changes observed in studies implementing DPP interventions in nonresearch settings in the United States.Methods and FindingsIn this systematic review and meta-analysis, we pooled data from studies in the United States implementing DPP lifestyle modification programs (focused on modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
91
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 66 publications
8
91
1
2
Order By: Relevance
“…This weight loss, corresponding to 8.2% of baseline weight, resulted in significant improvement of cardiometabolic and psychological parameters, ED, and QoL (tables 1, 2, 3). These results confirm previous observations reporting clinically meaningful health improvements after a moderate weight loss [29,30,31]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This weight loss, corresponding to 8.2% of baseline weight, resulted in significant improvement of cardiometabolic and psychological parameters, ED, and QoL (tables 1, 2, 3). These results confirm previous observations reporting clinically meaningful health improvements after a moderate weight loss [29,30,31]. …”
Section: Discussionsupporting
confidence: 92%
“…This relatively modest weight reduction was associated with favorable changes in blood pressure, plasma cholesterol, and glucose [29]. The analyzed studies retained the DPP's core principles of calorie-restricted diets and 150 min of moderate-intensity exercise per week, and mainly group sessions were administrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, life-style intervention programs should be intensive and have frequent follow-up to achieve significant weight reductions and improve clinical parameters such as lipid profile [24].Many studies found strong and consistent evidence that modest persistent weight loss can delay the progression from pre diabetes to type 2 diabetes [25,26] and is beneficial to the management of type 2 diabetes. Modest weight loss (reduction of 5% of initial body weight), has been shown to improve glycemic control and to reduce the need for glucose-lowering medications [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…2729 By using the state-transition Markov model, we assumed that a participant is always in one of a finite number of discrete health states (Markov states). 24 Accordingly, the model was designed to simulate the progression of a hypothetical closed cohort (men started at age 53 years and women at age 54 years, respectively, which were the average ages for WAW participants by sex) in terms of the reduced risk of developing a specific disease as members lost weight and proliferated corresponding health outcomes.…”
Section: Methodsmentioning
confidence: 99%